1994
DOI: 10.1037/0033-2909.115.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced eating.

Abstract: Stress is widely thought to lead to overeating. Studies of stress-induced eating have tested two models. One has tested whether stress increases eating in all exposed organisms and has been tested primarily with animals and physical stressors. The other has tested individual differences in vulnerability to stress-induced eating and has tested only human subjects and psychological stressors. The most consistent set of findings shows that "restrained" eating predicts vulnerability among women; we conclude that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
550
7
20

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 755 publications
(600 citation statements)
references
References 137 publications
(286 reference statements)
23
550
7
20
Order By: Relevance
“…29 Moreover, stress has an effect on eating behaviour by leading to decreased or increased food intake, which is related to severity and chronic nature of the applied stress. 49 Chronic Maternal educational level and NMB polymorphisms M Pigeyre et al stress elicits a more passive response driven by the hypothalamus-pituitary-adrenal axis, with increased cortisol secretion; 50 increasing food intake through neuropeptide-Y secretion and augmenting abdominal fat mass through adipose tissue lipoprotein lipase activation. 51 In contrast, increases in cortisol prompt people to consume hedonic, highly palatable foods that are energy dense and potentially contribute to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, stress has an effect on eating behaviour by leading to decreased or increased food intake, which is related to severity and chronic nature of the applied stress. 49 Chronic Maternal educational level and NMB polymorphisms M Pigeyre et al stress elicits a more passive response driven by the hypothalamus-pituitary-adrenal axis, with increased cortisol secretion; 50 increasing food intake through neuropeptide-Y secretion and augmenting abdominal fat mass through adipose tissue lipoprotein lipase activation. 51 In contrast, increases in cortisol prompt people to consume hedonic, highly palatable foods that are energy dense and potentially contribute to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have asserted that the experience of stress does not increase the consumption of food in non-restrained individuals (Greeno & Wing, 1994), a recent study suggests that even though stress does not affect the total amount of caloric intake it does increase the proportion of highly palatable 'comfort foods' ingested (Pecoraro, Reyes, Gomez, Bhagava, & Dallman, 2004). Also our own studies suggest that acute (but not chronic) stress increases the wanting of palatable food-which may act as a compensation for negative experiences and/or the restoration of the energy balance .…”
Section: Overweight In Modern Societymentioning
confidence: 99%
“…In adults, stress precedes weight gain (1), particularly gains in visceral fat (2,3). There is less research on stress and weight gain in children, but research in children has shown stress precedes weight gain (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Greeno and Wing (1) have developed the "general effects" and "individual differences" models for stress-induced eating. The "general effects" model has been tested predominately in small animals and hypothesizes that stress directly influences appetite in all subjects (1). The "individual differences" model has been developed from data in women who do not have eating disorders and suggests that stress-induced hyperphagia is a result of individual differences in several factors including restrained eating.…”
Section: Introductionmentioning
confidence: 99%